Conceptualização de "serra gaúcha" no discurso turístico publicitário - Keller, Garine Andrea (My University, 2014)
Serra Gaúcha is considered a dense area of tourist vocations tourist, historical-cultural, enogastronomy and industrial. Understanding "Serra Gaúcha" as the demarcation of certain regional areas, we start from the principle that it constitutes, according to a conceptualization process, as a conceptual category. Through means of Cognitive Linguistics, we analyze how the category SERRA GAUCHA is constructed on tourist advertising discourse. There are several forms of demarcation: cultural regions (due immigration traces), geography, tourism industry (division in micro tourist region following State Secretariat of Tourism) and sectorial groups of economic interests (furniture, metallurgical and wine). In this dissertation, we investigated different ways of categorizing the region named "Serra Gaúcha" a toponym from tourism sector perspective. We look forward to identify cognitive and cultural models underlying the discourses that constitute the corpus of study, compound of tourism advertising material of the Serra Gaúcha . It appears that the regional demarcations in tourist advertising discourse use metaphoric and metonymic models, which generate effects of prototypically. Specifically, Serra Gaúcha is conceptualized, metonymically, by reference to the products generated in the region, demarcating it as a potential consumer markets. Characteristics (metonymically or metaphorically) have a role in attracting tourists to a market of consumer choices: nature, cultural patrimony, gastronomy, typical products, among others.
A Serra Gaúcha é considerada uma área densa de vocações turística, histórico-cultural, enogastronômica e industrial. Entendendo Serra Gaúcha‟ como demarcação de determinados setores regionais, parte-se do princípio de que se constitua, segundo processos de conceptualização, como uma categoria conceitual. Assim, com o aparato da Linguística Cognitiva, analisa-se como essa categoria SERRA GAÚCHA é demarcada no discurso turístico publicitário. Há diversas formas de demarcação: regiões culturais (em função de traços da imigração), geografia, setor turístico (divisão em microrregiões turísticas conforme Secretaria do Turismo do Estado), agrupamentos em função de interesses econômicos (setor moveleiro, vinícola e metalúrgico). Nesta dissertação, investigam-se as diferentes formas de categorizar a região nomeada Serra Gaúcha‟ um topônimo pela perspectiva do setor turístico, com o objetivo de identificar os modelos cognitivos e culturais subjacentes aos discursos que constituem o corpus de estudo, composto de material de divulgação turística da Serra Gaúcha. Verifica-se que as demarcações regionais no discurso turístico publicitário fazem uso de modelos metafóricos e metonímicos, que geram efeitos de prototipicidade. Especificamente, SERRA GAÚCHA é conceptualizada, metonimicamente, por referência aos produtos gerados na região, demarcando-a como mercados potenciais de consumo. As características (metonimizadas ou metaforizadas) têm o papel de atrair o turista para um mercado de opções de consumo: natureza, patrimônio cultural, gastronomia, produtos "típicos", entre outros.
Keywords: LETRAS; Turismo; Publicidade; Serra gaúcha; Linguística cognitiva; Modelos cognitivos idealizados; Metonímia; Lexicologia; Nomes geográficos; Tourism; Advertising; Serra gaúcha; Cognitive linguistics; Cognitive idealized models; Metonymy; Lexicology; Names, geographical